KEMAMPUAN PUSTAKAWAN DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 (Studi Kasus Pustakawan Institut Agama Islam Sultan Muhammad Syafiuddin Sambas) - Zulfikar Ghazali (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
The purpose of this study was to determine the ability of librarians at the Sultan Muhammad Syafiuddin Sambas Islamic Institute and the efforts made in facing the era of the industrial revolution 4.0. This type of research is descriptive qualitative. Data obtained through interviews with sources. Meanwhile, the data analysis is qualitative inductive. For the research results, it can be seen that based on the librarian ability theory at the Sultan Muhammad Syafiuddin Sambas Islamic Institute, it can be concluded that first, librarians have the ability to understand and use information technology tools in the services available in the library. Second, librarians know the form and format of information sources as well as how to search for information. Third, librarians have the ability to analyze information obtained from the public and publish this information upon request. Fourth, the librarian knows the use of information technology tools in conducting or as a tool in conducting research. Fifth, Librarians are still not active in publishing scientific papers or scientific ideas using information technology tools. Sixth, librarians always make improvements and adjustments to developments in information technology, such as learning some soft skills consisting of website creation and graphic design applications. Seventh, librarians always innovate and design activities to improve services in the library. As for the efforts that have been made in facing the current era of the industrial revolution 4.0, namely first, all units in the library are open and accepting and trying to adapt to technological developments, one of which is using information technology in existing services in the library, one of which is the use of the Slims Senayan Bulian application. Second, the library has collaborated with various parties such as the National Library, the Indonesian Higher Education Library Forum - West Kalimantan, the Sambas Regional Library and PT. KUBUKU.